2019
DOI: 10.2147/cmar.s183355
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lipase member H is a downstream molecular target of hypoxia inducible factor-1&alpha; and promotes papillary thyroid carcinoma cell migration in BCPAP and KTC-1 cell lines</p>

Abstract: BackgroundPapillary thyroid carcinoma (PTC) is the most common type of thyroid carcinoma, which is associated with a high incidence of lymph-node metastasis. Multiple biomarkers have been identified for the precise diagnosis of PTC at an early stage. However, their role in PTC remains poorly elucidated. Previously, we reported that lipase H (LIPH), a membrane-bound protein, was highly expressed in PTC. This study aimed to fully elucidate the causal role of LIPH in the development of PTC and investigated its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Our data exhibited that Twist1 was dropped and E-cadherin was raised after circ_LDLR deficiency in PTC cells. LIPH has been demonstrated to be increased in PTC, and LIPH knockdown suppressed PTC cell colony formation, proliferation and metastasis [20]. Here, we confirmed that LIPH was a target gene of miR-195-5p.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our data exhibited that Twist1 was dropped and E-cadherin was raised after circ_LDLR deficiency in PTC cells. LIPH has been demonstrated to be increased in PTC, and LIPH knockdown suppressed PTC cell colony formation, proliferation and metastasis [20]. Here, we confirmed that LIPH was a target gene of miR-195-5p.…”
Section: Discussionsupporting
confidence: 76%
“…Cui et al declared that LIPH was associated with the tumor size, lymph node metastasis, and distant metastasis of breast cancer [19]. Moreover, a previous study demonstrated that LIPH could aggravate PTC development [20]. However, the underlying mechanisms of LIPH in PTC are not entirely understood.…”
mentioning
confidence: 99%
“…31 It was reported that hypoxia-inducible factor-1α (HIF-1α) gene expression was increased during hypoxic conditions in tumors, including PTC. 32 Furthermore, ANGPTL4 is known to be a gene induced by hypoxia. Studies have shown that HIF-1α directly up-regulated the expression of ANGPTL4 in hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…LIPH is a member of the mammalian triglyceride lipase family. The expression of LIPH was found to be involved in papillary thyroid carcinoma development (54) and mRNA level of LIPH may act as a prognostic marker for esophageal adenocarcinoma, lung cancer and breast cancer (55)(56)(57). Study demonstrated that CIRH1A plays regulatory roles in proliferation and apoptosis of colorectal cancer cell (58).…”
Section: Liphmentioning
confidence: 97%